Peran Fasilitator Pendamping Pada Implementasi Program Bestee Kepada Nasabah BTPN Syariah MMS Jogoroto Jombang - Melfiya Rosita; Perdana, Putra; Huda, Syamsul (Lembaga Dongan Dosen, 2024)
Bank BTPN Syariah provides various financing products and services and opens access to financial services for productive underprivileged women to obtain business capital, as well as providing training and mentoring. Bank BTPN Syariah continues to collaborate with various parties including students through the